Simulation Study on Electrical Resistance Tomography using Metal Wall for Bubble Detection - Suzanna, Ridzuan Aw; Ruzairi, Abdul Rahim; Mohd Hafiz, Fazalul Rahiman; Elmy Johana, Mohamad; Fazlul Rahman, Mohd Yunus; Yasmin, Abdul Wahab; Naizatul Shima, Mohd Fadzil; Juliza, Jamaludin (Penerbit Universiti Teknologi Malaysia, 2015)
Industrial process pipelines are mostly known to be constructed from metal which is a conducting material. Bubbles or gas detection are crucial in facilitating the bubble columns performance. By employing the Electrical Resistance Tomography (ERT) technique, a simulation study using COMSOL has been conducted to investigate the effect of excitation strategy, bubble sizes and locations towards the metal wall system. As for the current excitation strategy, conducting boundary protocol has to be applied when it comes to metallic vessel to overcome the grounding effect. Bubbles with a greater size than 2 mm and especially the one that is located near the wall boundary are much easier to detect. Further potential improvements to the current design and image reconstruction of the ERT system are desirable to improve the detection of small and centred bubble.